Identification of Three Residues Essential for 5-Hydroxytryptamine 2A-Metabotropic Glutamate 2 (5-HT2A·mGlu2) Receptor Heteromerization and Its Psychoactive Behavioral Function - Moreno, José L.; Muguruza, Carolina; Umali, Adrienne; Mortillo, Steven; Holloway, Terrell; Pilar-Cuéllar, Fuencisla; Mocci, Giuseppe; Seto, Jeremy; Callado, Luis F.; Neve, Rachael L.; Milligan, Graeme; Sealfon, Stuart C.; et al. (The Journal of biological chemistry, 2012)
Serotonin and glutamate G protein-coupled receptor (GPCR) neurotransmission affects cognition and perception in humans and rodents. GPCRs are capable of forming heteromeric complexes that differentially alter cell signaling, but the role of this structural arrangement in modulating behavior remains unknown. Here, we identified three residues located at the intracellular end of transmembrane domain four that are necessary for the metabotropic glutamate 2 (mGlu2) receptor to be assembled as a GPCR heteromer with the serotonin 5-hydroxytryptamine 2A (5-HT2A) receptor in the mouse frontal cortex. Substitution of these residues (Ala-6774.40, Ala-6814.44, and Ala-6854.48) leads to absence of 5-HT2A·mGlu2 receptor complex formation, an effect that is associated with a decrease in their heteromeric ligand binding interaction. Disruption of heteromeric expression with mGlu2 attenuates the psychosis-like effects induced in mice by hallucinogenic 5-HT2A agonists. Furthermore, the ligand binding interaction between the components of the 5-HT2A·mGlu2 receptor heterocomplex is up-regulated in the frontal cortex of schizophrenic subjects as compared with controls. Together, these findings provide structural evidence for the unique behavioral function of a GPCR heteromer. The 5-HT2A·mGlu2 receptor heterocomplex is involved in psychosis. Substitution of Ala-6774.40, Ala-6814.44, and Ala-6854.48 in mGlu2 abolishes the behavioral effects of hallucinogenic 5-HT2A agonists. Three residues at transmembrane domain 4 of mGlu2 are necessary to form the 5-HT2A·mGlu2 receptor heterocomplex. These results provide insight into the structure and behavioral function of the 5-HT2A·mGlu2 receptor heterocomplex.